STRATEGI PEMBELAJARAN NILAI ISLAM DALAM PEMBENTUKAN KARAKTER RELIGIUS DI SDIT TAQIYYA ROSYIDA - Pahesti Galuh Prasetyani; Kustiarini Kustiarini; Fauzi Muharom; Siti Choiriyah (Jurnal Pendidikan Sultan Agung, 2025)
The formation of religious character from an early age is an important focus in Islamic value-based education, especially in elementary schools. However, the application of these values is often still formal and does not touch on real practices. This study aims to identify and explore Islamic value-based learning strategies through religious projects implemented at SDIT Taqiyya Rosyida. The study used a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study showed that the habit of daily worship, teacher role models, integration of Islamic values in subjects, and religious projects such as Ramadhan Berbagi and the tahfidz program were the main strategies in instilling the values of honesty, empathy, responsibility, and discipline in students. This strategy is also supported by a conducive school environment and collaboration with parents. In conclusion, Islamic value-based learning strategies that are implemented consistently and contextually are effective in forming students' religious character as a whole.